Analysis of The Impact of Wind and The Environmental Temperature on The Performance of a Rooftop Solar PV System: A Case Study of 52,2 kWp PT PLN Research and Development Center Rooftop PV Systems: Analisis Pengaruh Angin dan Suhu Lingkungan Terhadap Kinerja Sistem PV Surya Atap: Studi Kasus 52,2 kWp Pusat Penelitian dan Pengembangan PT PLN Sistem PV Atap - Agussalim Syamsuddin (Fakultas Teknik, Universitas Brawijaya, 2023)
This study aimed to observe the influence of weather parameters (irradiation, ambient temperature, PV module temperature, wind speed, and direction). Performance evaluation of rooftop PV systems is carried out according to IEC 61724-1:2017. The parameters measured are solar irradiance using a pyranometer, the surface temperature of the PV module using a temperature sensor, ambient temperature, wind speed, and direction using the Smart Weather Sensor Lufft type WS500-UMB. The analysis was performed under three different weather conditions: cloudy, rainy, and sunny skies. In rainy conditions, the highest efficiency of the PV array is 16.1% – 16.69%, because the environmental temperature and the temperature of the PV module when it rains is the lowest compared to sunny and cloudy conditions. In sunny skies, the highest inverter efficiency is obtained, around 97.9 – 98.84%, this is due to very high solar irradiation (more than 1000 W/m²), so the inverter works more optimally than in rainy and cloudy conditions. The highest average wind speed is obtained in sunny conditions, which is 3.28 m/s with the same wind direction, namely the West-Northwest, but the influence of the wind is not significant to provide a cooling effect to the rooftop PV.